Phytochemical and biological evaluation of methanolic extracts as a preventive measure for antioxidant and Anticoccidial Eimeria columbae Oocysts - Mutee Murshed; Jameel Al-Tamimi; Khalid Elfaki Ibrahim; Saleh Al-Quraishy (PLoS ONE, 2026)
Background Herbal products are rich in the source of bioactive ingredients, including phenols, flavonoids, tannins, and essential oil components such as cinnamaldehyde, eugenol, and 1,8-cineole, and have significant potential for therapeutic applications that are associated with antioxidant and anticoccidial activities. Aims This study aimed to investigate the phytochemical quantification and antioxidant anticoccidial assay in methanolic extracts of Cinnamomum verum and Laurus nobilis . Methods Total phenol, flavonoid, and tannin content was measured using standard spectrophotometric methods. Phytochemical properties were characterized using Fourier transform infrared spectroscopy (FTIR). Antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and (2,2-diphenyl-1-picrylhydrazyl (ABTS) free radical scavenging assays. In vitro anticoccidial activity was assessed using seven concentrations : 10, 25, 50, 100, 150, and 200 mg/mL of C. verum and L. nobilis , in addition to K₂Cr₂O₇ as the control at 24, 48, 72, and 96 hours. Results FTIR analysis revealed characteristic absorption bands in the C. verum and L. nobilis extracts, indicating the presence of diverse functional groups associated with phenolic and related phytochemical constituents, as evidenced by their characteristic absorption bands across the 400–4000 cm ⁻ ¹ range. All extracts contained measurable levels of phenols, flavonoids, and tannins. The highest total phenolic content was recorded in C. verum (63.56 ± 0.552 mg/g dry weight) and L. nobilis (57.40 ± 6.05 mg/g dry weight). All extracts exhibited strong antioxidant activity, with IC₅₀ values for DPPH (12.59 ± 0.51 and 30.32 ± 3.22 μg/mL) and ABTS (13.95 ± 0.35, 19.56 ± 4.89 μg/mL) assays to C. verum and L. nobilis . The extracts exhibited dose- and time-dependent inhibition of E. columbae sporulated oocysts, at 200 mg/ml, 75.67% at C. verum and 72.57% at L. nobilis (p < 0.05) at higher concentrations at 96 h, alongside increased oocyst destruction of ~12%. Conclusion The findings demonstrated that the extracts of C. verum and L. nobilis leaves contain bioactive phytochemicals that inhibit coccidia oocysts in vitro, suggesting a potentially effective and safe natural option for managing coccidiosis in Domestic Pigeons.